2014
DOI: 10.1155/2014/368107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietaryn-3Polyunsaturated Fatty Acids on Oxidant/Antioxidant Status in Macrosomic Offspring of Diabetic Rats

Abstract: The aim of this work was to determine the effect of dietary n − 3 PUFA on oxidant/antioxidant status, in vitro very low and low density lipoprotein (VLDL-LDL), and VLDL-LDL-fatty acid composition in macrosomic pups of diabetic mothers. We hypothesized that n − 3 PUFA would improve oxidative stress in macrosomia. Diabetes was induced in female Wistar rats fed with the ISIO diet (control) or with the EPAX diet (enriched in n − 3 PUFAs), by streptozotocin. The macrosomic pups were killed at birth (day 0) and at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 47 publications
(82 reference statements)
2
5
0
Order By: Relevance
“…In line with previous findings, this study also demonstrated that FO could protect against protein and lipid damage in groups that received fructose solution (MS) (Guermouche and others ; Pilar and others ). Furthermore, flaxseed lignan SDG protection against oxidative damage to lipids agrees with results of Newairy and Abdou ().…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous findings, this study also demonstrated that FO could protect against protein and lipid damage in groups that received fructose solution (MS) (Guermouche and others ; Pilar and others ). Furthermore, flaxseed lignan SDG protection against oxidative damage to lipids agrees with results of Newairy and Abdou ().…”
Section: Discussionsupporting
confidence: 92%
“…PUFAs have been linked to considerable cardiovascular benefits in diabetics and heart failure patients [ 177 , 178 , 179 ]. Consistent with the above, a rat model of diabetes shows that PUFAs alter favorably the lipid metabolism in diabetic rats themselves and on the oxidation level of their offspring [ 180 ]. This fatty acid acts as an indirect anti-oxidant in vascular endothelial cells and reduced inflammation and levels of adhesion molecules, in turn diminish the risk of atherosclerosis and cardiovascular disease [ 181 ].…”
Section: Therapeutic Perspectives For Diabetic Cardiovascular Disementioning
confidence: 56%
“…3a-d and S45 †). [86][87][88][89] The changes in blood glucose levels of the diabetic rats as a function of time following oral administration of various formulations or subcutaneous injection of free-form insulin solution were determined (Fig. 3ad and S45 †).…”
Section: Resultsmentioning
confidence: 99%